The validation of assessment for learning audit instrument: a mixed methods approach - Mazidah Mohamed,; Mohd Sallehhudin Abd Aziz,; Kemboja Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The CEFR-aligned curriculum promotes integration in the implementation of Assessment for Learning (AfL) by English language teachers in primary schools. This paper depicts the mixed methods pilot and validation of the Assessment for Learning Audit Instrument (AfLAi) for the purpose of examining the use and understanding of AfL among the teachers in primary schools. In Phase 1, three subject matter experts were consulted, and nine English language teachers provided consensual validation. In Phase 2, 53 English language teachers responded to the adapted instrument. AfLAi was further discussed with the validators in Phase 3. This procedure was adapted from Phase 8 of the Instrument Development and Construct Validation mixed research techniques. Among the emerging themes were on language correction, item/ instrument difficulty, and useful items. The quantitative data was compared with the scales from the original authors regarding the four key strategies of AfL in AfLAi: Sharing Learning Intentions and Success Criteria, Questions and Classroom Discussions, Feedback and Peer- and Self- Assessment. Based on the mixed data arranged in a joint display, some parts in the items were adapted to accommodate the local context. Among the findings were (i) the key strategy known as Learning Intentions in AfLAi was not applicable in the target context, and (ii) some examples in the items needed to be changed to fit the Malaysian syllabus. The implications of this pilot study and validation process included 16 changes in the instrument and the translation of the instrument into Bahasa Melayu.